Transcription Factor HBP1 Enhances Radiosensitivity by Inducing Apoptosis in Prostate Cancer Cell Lines. (28th January 2016) - Chen, Yicheng; Wang, Yueping; Yu, Yanlan; Xu, Liwei; Zhang, Youyun; Yu, Shicheng; Li, Gonghui; Zhang, Zhigeng
Abstract : Radiotherapy for prostate cancer has been gradually carried out in recent years; however, acquired radioresistance often occurred in some patients after radiotherapy. HBP1 (HMG-box transcription factor 1) is a transcriptional inhibitor which could inhibit the expression of dozens of oncogenes. In our previous study, we showed that the expression level of HBP1 was closely related to prostate cancer metastasis and prognosis, but the relationship between HBP1 and radioresistance for prostate cancer is largely unknown. In this study, the clinical data of patients with prostate cancer was compared, and the positive correlation was revealed between prostate cancer brachytherapy efficacy and the expression level of HBP1 gene. Through research on prostate cancer cells in vitro, we found that HBP1 expression levels were negatively correlated with oncogene expression levels. Furthermore, HBP1 overexpression could sensitize prostate cancer cells to radiation and increase apoptosis in prostate cancer cells. In addition, animal model was employed to analyze the relationship between HBP1 gene and prostate cancer radiosensitivity in vivo; the result showed that knockdown of HBP1 gene could decrease the sensitivity to radiation of xenograft. These studies identified a specific molecular mechanism underlying prostate cancer radiosensitivity, which suggested HBP1 as a novel target in prostate cancer radiotherapy.